2015
DOI: 10.1112/jlms/jdv035
|View full text |Cite
|
Sign up to set email alerts
|

p-parts of character degrees

Abstract: We show that if p is an odd prime and G is a finite group satisfying the condition that p 2 divides the degree of no irreducible character of G,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The dual of the Ito-Michler theorem on the set of conjugacy class sizes is that every conjugacy class of G has p -size if and only if a Sylow p-subgroup of G is central. In this paper, we study the dual versions of the results of Lewis et al on the set of conjugacy class sizes and show that analogues of the main results of [3] and [2] hold.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The dual of the Ito-Michler theorem on the set of conjugacy class sizes is that every conjugacy class of G has p -size if and only if a Sylow p-subgroup of G is central. In this paper, we study the dual versions of the results of Lewis et al on the set of conjugacy class sizes and show that analogues of the main results of [3] and [2] hold.…”
Section: Introductionmentioning
confidence: 83%
“…In particular, this implies that |G : F(G)| p = 1, where F(G) is the Fitting subgroup of G. A natural generalisation of the Ito-Michler theorem is the following result of Lewis et al [3]: if G is solvable and e p (G) = 1, then |G : F(G)| p ≤ p 2 . In [2], Lewis et al studied a similar problem for arbitrary finite groups and showed that if G is finite and e p (G) = 1, then |G :…”
Section: Introductionmentioning
confidence: 99%
“…Clearly P Out (S). Since S is a p‐group, we know (see for example [, Lemma 2.3]) that PS/S is a normal cyclic subgroup of G/S. Let P1 be a subgroup of P of order p.…”
Section: Proposition Bmentioning
confidence: 99%
“…The results in the next lemma are due to Gagola (see or ). Lemma Let S be a nonabelian simple group and let G be an almost simple group with SG Aut (S).…”
Section: Proposition Amentioning
confidence: 99%
See 1 more Smart Citation